How to reach and teach ADD/ADHD children : practical techniques, strategies, and interventions for helping children with attention problems and hyperactivity - Rief, Sandra F. (Center for Applied Research in Education, 1993)
What is ADD/ADHD? Critical factors in working with ADD?ADHD children. A list of don'ts. A comprehensive treatment program for ADD?ADHD. Preventing behavioral problems in the classroom through management techniques...